Towards defining and advancing ‘Made in Africa Evaluation’ - Oladayo Omosa (AOSIS, 2021)
Background: Most evaluation in Africa is rooted in dominant neoliberal Western approaches. Imported Western evaluation frames may lack multicultural validity and can lead to wrong conclusions and poor development outcomes. They may also reinforce subjugation and cultural hegemony through neo-imperialism and colonisation of the imaginations of those concerned. The Made in Africa Evaluation (MAE) concept has received attention in recent years as a way to address this challenge. As a relatively nascent construct, however, interested scholars and professionals continue to seek to define and operationalise MAE more effectively.